Thrombosis and COVID-19: The Potential Role of Nutrition - Tsoupras, Alexandros; Lordan, Ronan; Zabetakis, Ioannis (Frontiers in Nutrition, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the coronavirus disease (COVID-19), is a contagion that has rapidly spread around the globe. COVID-19 has caused significant loss of life and disrupted global society at a level never before encountered. While the disease was predominantly characterized by respiratory symptoms initially, it became clear that other systems including the cardiovascular and neurological systems were also involved. Several thrombotic complications were reported including venous thrombosis, vasculitis, cardiomyopathy, and stroke. Thrombosis and inflammation are implicated in various non-communicable diseases (NCDs). This is of significant concern as people with pre-existing conditions such as cardiovascular disorders, renal disorders, obesity, metabolic syndrome, and diabetes are at greater risk of severe COVID-19 infection. Consequently, the research surrounding the use of anticoagulants, antiplatelet, and antithrombotic strategies for prophylaxis and treatment of COVID-19 is of critical importance. The adoption of a healthy diet, physical exercise, and lifestyle choices can reduce the risk factors associated with NCDs and the thrombo-inflammatory complications. In this review, these thrombotic complications and potential foods, nutraceuticals, and the antithrombotic constituents within that may prevent the onset of severe thrombotic complications as a result of infection are discussed. While nutrition is not a panacea to tackle COVID-19, it is apparent that a patient’s nutritional status may affect patient outcomes. Further intensive research is warranted to reduce to incidence of thrombotic complications.